WOMEN ENTREPRENEURS IN MANIPUR: PATHWAYS TO EMPOWERMENT AND ECONOMIC INDEPENDENCE - Kangjam Dijita Devi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Entrepreneurship is crucial for societal growth, fostering long-term business ownership, employment creation, and socioeconomic security, especially for women. This study aimed to: a) examine the differences in entrepreneurship tendencies among women entrepreneurs based on age, habitat, and education; b) investigate the differences in empowerment levels of women entrepreneurs based on age, habitat, and education; and c) analyze the relationship between entrepreneurship tendencies and the empowerment of women entrepreneurs. Using a descriptive survey design, 200 women entrepreneurs from Manipur were selected through simple random sampling. The Entrepreneurship Characteristics/Tendencies Scale and Women Empowerment Measure (WoEm-M) were utilized to measure entrepreneurship tendencies and empowerment levels, respectively. Findings revealed that most women entrepreneurs in Manipur have medium to high levels of entrepreneurial characteristics, indicating a robust entrepreneurial presence. Urban women entrepreneurs exhibited stronger entrepreneurship tendencies compared to their rural counterparts, while age and education did not significantly influence these characteristics. Similarly, urban women showed higher empowerment levels than rural women, with age and education having no significant effect. A significant positive correlation was found between entrepreneurship tendencies and women empowerment, underscoring the potential benefits of enhancing entrepreneurial traits for women’s empowerment.